Implementation of an IoT-Based Smart Water System as a Means in Monitoring the Use of Consumer Water Debit Using Photovoltaic in Seboro Village Probolinggo - Moh Zainul Falah; Abdullah Iskandar Syah; Wahyu Tri Handoko; Nanik Nor Laila; Faizah Nur Faridah; Muladi Muladi (CV. Creative Tugu Pena, 2023)
Seboro Village, which is located in Probolinggo Regency, has a BUMDES whose business unit is the “Sumber Abadi” Drinking Water Supply Facility Management Group (KP.SPAM). The group is engaged in the field of consumption water which will be used by the people of Seboro Village who subscribe. In its implementation, the manager will monitor the use of conventional consumer water discharge by coming to each house that subscribes as a step to calculate the cost of billing water usage per month. This community service activity program aims to make it easier for water managers to monitor the use of consumer water discharge in the